(untitled) (Eurasian Journal of Ecology, 2024)
The growth of industrial production leads to an increase in the volume of waste generated and the costs of their storage, concentration, burial, disposal, capture or neutralization, especially in the non-ferrous metallurgy of Kazakhstan. The metallurgical production system is based on technological processes that actively interact with the environment. The bulk of existing technological processes are built on the principle of open systems, on the one hand consuming raw materials and energy, and on the other - producing finished products and waste. Taking into account the current level of production, a significant period of time is still required to significantly reduce production waste associated with the improvement of technological processes. During these periods, waste accumulating in industrial and other territories continues to intensively pollute the soil, air and water sources. The purpose of the work: Utilization of man-made industrial waste and development of technological bases for the production of composite cements based on them. The use of waste "carbonate-barium tailings", phosphoric and blast furnace slags in the production of composite cements, on the one hand, improves the ecological situation of the region, and on the other hand, allows us to save reserves of natural resources for future generations, especially non-renewable ones, and prevent the destruction of natural landscapes with natural self-development. In the course of the work, standard and generally accepted research methods were carried out: chemical and mineralogical methods of analysis, scanning electron microscopy, physical and mechanical tests. Key words: utilization of waste carbonate-barium tailings, technogenic waste, resource conservation, energy conservation, phosphoric and blast furnace slag, environmental damage, composite low-clinker finely ground cement.